2021
DOI: 10.1088/1757-899x/1014/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of a low alloyed Cu-Cr-Zr alloy after ECAP-Conform

Abstract: The microstructure of a Cu-0.1%Cr-0.1%Zr alloy after annealing or aging and equal channel angular pressing with conform (ECAP-C) process was investigated. ECAP-C led to formation of strain induced low-angle boundaries (LAB) which transformed in high-angle boundaries (HAB) during deformation. Deformation microbands developed after 1 ECAP-C pass, leading to new ultrafine grain formation in the microbands upon further processing. Average grain size gradually decreased with strain while dislocation density increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the EBSD pattern, small recrystallized grains ~2 μm to 3 μm in size were observed within the band boundaries (Figure 2). This type of dynamic recrystallization directed along the boundaries of the bands is continuous [11][12][13].…”
Section: (C))mentioning
confidence: 99%
“…In the EBSD pattern, small recrystallized grains ~2 μm to 3 μm in size were observed within the band boundaries (Figure 2). This type of dynamic recrystallization directed along the boundaries of the bands is continuous [11][12][13].…”
Section: (C))mentioning
confidence: 99%
“…Morozova et al have investigated the microstructural of a Cu-0.1%Cr-0.1%Zr alloy after the ECAP-Conform process. It was found that during deformation the high-angle boundaries (HAB) transformed to low-angle boundaries (LAB) due to the strain-induced of the ECAP-Conform process [14]. Shahab et al [15] compared the distribution of equivalent plastic strain after the continuous confined strip shearing (C2S2) and the ECAP-Conform processes for 1100 Al numerically.…”
Section: Introductionmentioning
confidence: 99%